2013
DOI: 10.1016/j.pediatrneurol.2013.03.006
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Magnetic Resonance Imaging Findings in Children Born Extremely Preterm, Very Preterm, and at Term

Abstract: The extremely preterm, very preterm, and term subjects shared the same morphological pathology, revealing no specific preterm MRI pattern, but both premature cohorts had higher frequencies. Differences were mainly limited to mild pathology. Whether MRI lesions were more common in the extremely preterm than in the very preterm group is uncertain as the difference in frequency was similar in the two control groups, suggesting a lack of objective criteria for differentiating mild pathology from normality or that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 87 publications
1
8
0
1
Order By: Relevance
“…The absence of a specific preterm MRI pattern was previously suggested [47], when comparing extremely preterm born children and very preterm 19-year olds with age matched controls. Like the present study, they found ventricular dilatation, white matter affection and thinning of the corpus callosum in the preterm born groups but all three groups shared the same morphological pathology, albeit with higher frequencies in premature cohorts [47].…”
Section: Discussionmentioning
confidence: 74%
“…The absence of a specific preterm MRI pattern was previously suggested [47], when comparing extremely preterm born children and very preterm 19-year olds with age matched controls. Like the present study, they found ventricular dilatation, white matter affection and thinning of the corpus callosum in the preterm born groups but all three groups shared the same morphological pathology, albeit with higher frequencies in premature cohorts [47].…”
Section: Discussionmentioning
confidence: 74%
“…This difference is mainly related to the fact that the prenatal and perinatal conditions that are associated with a shorter gestation are generally more unfavorable, compared with those that are associated with a longer gestation. Numerous previous studies have shown evidence that neurological impairment and developmental disabilities are related to gestation, and are generally more common and more severe in children born extremely premature than in those born late or very premature (16)(17)(18)(19)(20).…”
Section: Discussionmentioning
confidence: 99%
“…Meta-analyses reveal reductions of total brain volume, white and gray matter, cerebellum, hippocampus, caudate and corpus callosum, 2,3 and these changes seem to persist into adolescence. [4][5][6][7][8][9][10] Alterations in brain structures correlate with intellectual and motor abilities in preterm infants. [11][12][13][14] The neuropathology of brain development in premature infants reflects multiple factors.…”
Section: What This Study Addsmentioning
confidence: 99%